FAKTOR-FAKTOR YANG DIPERTIMBANGKAN WISATAWAN MENGGUNAKAN JASA ONLINE BOOKING BERBASIS APLIKASI TRAVELOKA DI EPISODE HOTEL KUTA BALI - Carina Maylanie Jeanne Paparang; Saortua Marbun; Ni Made Ernila Junipisa (Journal Research of Management, 2026)
This study aims to identify the various factors considered by tourists when using online booking services via the Traveloka application at Episode Hotel Kuta Bali, as well as to determine the most dominant factor. The research design employs a quantitative descriptive analysis using SPSS version 24 as the analytical tool. The study involves 85 respondents selected through purposive sampling. The research method applied is based on factor analysis, with data collected through interviews, documentation, and questionnaires. The results show that only 16 out of the 17 independent variables can be further analyzed. After the factor rotation process, five main components were identified. The naming of each new factor was determined based on the variables forming that factor. The first factor is corporate image, which has the highest eigenvalue of 5.558 and explains 34.756% of the total variance. The second factor is the marketing mix, with an eigenvalue of 2.520 and a variance percentage of 15.750%. The third is the brand factor, with an eigenvalue of 2.400 and a total variance of 15.000%. The fourth is the socio-cultural factor, which has an eigenvalue of 1.823 and a total variance of 11.394%. The fifth factor is the individual factor, with an eigenvalue of 1.304, accounting for 8.147% of the total variance. The implication for the company is to ensure the accuracy and suitability of room data displayed on the Traveloka application so that customers receive accurate information regarding room availability. Additionally, it is important to consistently maintain both service quality and the quality of the application itself.